2005
DOI: 10.1021/ja0514848
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and 2D Self-Assembly of CdSe Quantum Dots at the Air−Water Interface

Abstract: Langmuir film properties, UV-vis spectroscopy, epifluorescence microscopy, and transmission electron microscopy were used to study CdSe quantum dots (QDs) in 2D. By combining these results, it was possible to determine the molar absorptivity, limiting nanoparticle area, luminescence property, and arrangement of the QDs in the monolayer films at the air-water interface. Either trioctylphosphine oxide (TOPO) or 1-octadecanethiol (ODT) stabilized the QDs. The data collected reveal that TOPO forms close-packed mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 46 publications
1
69
0
Order By: Relevance
“…For example, both the airliquid and liquid-liquid interfaces have been widely exploited for the preparation of thin films of metals or semiconductors. [4,8,9,49] In particular, at the air-liquid interface (as in a Langmuir trough), thin films of CdSe quantum dots, [50] platinum nanoparticles, [51] gold clusters, [52] silver nanoparticles, [53] magnetic Fe 3 O 4 nanoparticles, [54] BaCrO 4 nanorods, [55] ZnS nanorods, [56] silver nanowires, [57] and carbon nanotubes [58] have been prepared. Furthermore, Langmuir-Blodgett (LB) techniques, that is, the transfer of an assembly at the water-air interface to a solid surface, has been broadly used to achieve closely packed thin films.…”
Section: Thin Films At Air-liquid Interfacesmentioning
confidence: 99%
“…For example, both the airliquid and liquid-liquid interfaces have been widely exploited for the preparation of thin films of metals or semiconductors. [4,8,9,49] In particular, at the air-liquid interface (as in a Langmuir trough), thin films of CdSe quantum dots, [50] platinum nanoparticles, [51] gold clusters, [52] silver nanoparticles, [53] magnetic Fe 3 O 4 nanoparticles, [54] BaCrO 4 nanorods, [55] ZnS nanorods, [56] silver nanowires, [57] and carbon nanotubes [58] have been prepared. Furthermore, Langmuir-Blodgett (LB) techniques, that is, the transfer of an assembly at the water-air interface to a solid surface, has been broadly used to achieve closely packed thin films.…”
Section: Thin Films At Air-liquid Interfacesmentioning
confidence: 99%
“…An important issue for the practical use of these materials as building blocks for photonic, electronic or magnetic devices is the assembly of semiconductor QDs in larger nanostructures [3]. Self-assembly methods have shown great potential for the "bottom-up" construction of such nanostructures [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that surface-modified hydrophobic colloidal nanoparticles may be organized at the air-water interface, and that multilayer films of the nanoparticles can be formed on various substrates by this technique [10,11]. The LB technique has already been used by several groups to form films of materials such as gold [8], silver [12], CdS [13], and CdSe [3] QDs.…”
Section: Introductionmentioning
confidence: 99%
“…Leblanc and coworkers studied a Langmuir film of CdSe quantum dots coated with trioctylphosphine oxide or 1-octadecanethiol. [61] Trioctylphosphine oxide forms close-packed monolayers of the quantum dots on the surface, while 1-octadecanethiol-stabilized quantum dots undergo interdigitation of alkyl chains. They adopted a new technique for prevention of three-dimensional aggregate formation, which entails addition of excess surfactants.…”
Section: Lb Films Of Zero-dimensional Spherical Nanoparticlesmentioning
confidence: 99%